Adsorption : progress in fundamental and application research : selected reports at the 4th Pacific Basin Conference on Adsorption Science and Technology : Tianjin, China, 22-26 May 2006 - Zhou, Li (World Scientific, 2007)
Adsorption is the basis of various emerging technologies that will be essential for addressing the problems of technologies that will be essential for addressing the problems of energy conservation and environmental protection. This volume reviews recent progress and outlines the outlook for future development in adsorption theories, kinetics, pressure swing adsorption, SMB, and new nanoporous adsorbents. The contributions cover the fundamental knowledge and methodologies for adsorption experiments and calculations regarding equilibria, heat effects, adsorbent structural modeling, diffusion measurement, and selectivity control. The volume also includes topics concerning hydrogen storage, desulfurization of fuels, and chiral separation. The contributors are internationally renowned scholars in the field of adsorption.
Keywords: Adsorption -- Congresses.; Chemical engineering -- Congresses.; Adsorption -- Congrès.; Génie chimique -- Congrès.; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical.; SCIENCE -- Chemistry -- Industrial & Technical.; Adsorption; Chemical engineering; Conference papers and proceedings